2017
DOI: 10.5664/jcsm.6816
|View full text |Cite
|
Sign up to set email alerts
|

Non-24-Hour Sleep-Wake Rhythm Disorder and Melatonin Secretion Impairment in a Patient With Pineal Cyst

Abstract: We report the case of a 14-year-old girl with a wide non-compressive pineal cyst, associated with the inability to control her sleep-wake schedule. Actigraphic monitoring showed a 24-hour free-running disorder (tau 26.96 hours). A 24-hour serum melatonin curve assay, with concomitant video-polysomnographic and body-core temperature monitoring, was performed. Melatonin curve showed a blunted nocturnal peak, lower total quantity of melatonin, and prolonged melatonin secretion in the morning, with normal temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 12 publications
2
11
0
1
Order By: Relevance
“…Pineal cysts potentially influence melatonin production; however, this has only been observed in a case report and in another small patient sample. 4,5 In support of this, we found men with pineal cysts and/or calcifications had higher | 493 mean melatonin than men without pineal calcification or cyst. We also observed men with calcification and cyst had lower risk for advanced prostate cancer, compared to men with no calcifications or cysts.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Pineal cysts potentially influence melatonin production; however, this has only been observed in a case report and in another small patient sample. 4,5 In support of this, we found men with pineal cysts and/or calcifications had higher | 493 mean melatonin than men without pineal calcification or cyst. We also observed men with calcification and cyst had lower risk for advanced prostate cancer, compared to men with no calcifications or cysts.…”
Section: Discussionsupporting
confidence: 69%
“…Pineal calcification has been reported both to have no effect on melatonin levels and to have been associated with lower melatonin levels, 2,3 and the effect of pineal cysts on melatonin levels has only been reported for small case reports (N <5), which differ in their findings. 4,5 Our group previously found a positive association between pineal parenchyma volume and 6-sulfatoxymelatonin levels in a sample of 122 men from the Age, Gene/ Environment Susceptibility-Reykjavik (AGES-Reykjavik) Study, an Icelandic cohort. 6 Other studies with small sample sizes have also reported positive correlations between pineal gland volume and melatonin levels, as measured in urine, plasma, and saliva.…”
Section: Introductionmentioning
confidence: 99%
“…They are linked to physiological dysfunctions of internal clock, circadian cycle or hormonal systems involved, like dopaminergic system and melatonin [1][2][3][4][5] . SD are often associated with age related comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…Sleep disorders (SD) are among the most studied neurological outcomes since the last 20 years. They have many psychosocial aetiologies like lifestyle, night shift, sporadic daily stressors or environmental stress; and obviously they are linked to physiological dysfunctions of internal clock, circadian cycle or hormonal systems involved, like dopaminergic system and melatonin (Baron and Reid, 2014, Borbely, 1982, Diez-Garcia and Garzon, 2017, Ferri et al, 2017, Leger and Ogrizek, 2012. SD are often associated with comorbidities depending of age.…”
Section: Introductionmentioning
confidence: 99%